PENINGKATAN KEMAMPUAN GURU DALAM PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) UNTUK PEMBELAJARAN DARING MELALUI WORKSHOP DI UPTD SDN AENGSAREH 1 KECAMATAN SAMPANG KABUPATEN SAMPANG - Moh. Nizar (re-JIEM (Research Journal of Islamic Education Management), 2021)
The Covid-19 pandemic requires online learning through various information technology-based media. The fact is that not all teachers at UPTD SDN Aengsareh 1 Sampang District can use it. Therefore, the implementation of this school action research aims to solve these problems. The results showed that the workshop activities could improve the ICT skills of teachers in online learning at UPTD SDN Aengsareh 1 Sampang District. This is evidenced in the implementation of school action research consisting of 2 cycles showing in the first cycle after the workshop the test results obtained are 1 out of 9 teachers or 11.11% in the low category, 5 out of 9 teachers or 55.56 in the medium category, and 3 teachers or 33.33% categorized as high. This situation must be continued in cycle II, because it has not reached the expected success indicator, which is 70% in the high category. After the second cycle was carried out, the following data were obtained: From 9 teachers there were 0 teachers or 0% in the low category, 2 teachers or 22.22% in the medium category, and 7 teachers or 77.78% in the high category. Therefore, the cycle was stopped, because it had reached the expected success indicator, which was 70% in the high category. This shows that the workshop can improve the ability of teachers in mastering ICT for online learning.